2014
DOI: 10.1002/num.21879
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of particle methods for structured population models with nonlocal boundary term in the framework of bounded Lipschitz distance

Abstract: Recently developed theoretical framework for analysis of structured population dynamics in the spaces of nonnegative Radon measures with a suitable metric provides a rigorous tool to study numerical schemes based on particle methods. The approach is based on the idea of tracing growth and transport of measures which approximate the solution of original partial differential equation. In this article, we present analytical and numerical study of two versions of Escalator Boxcar Train algorithm which has been wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Importantly, this study also found that insufficiently frequent internalizations may cause a failure in the ODEs describing the boundary cohort (Gwiazda et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, this study also found that insufficiently frequent internalizations may cause a failure in the ODEs describing the boundary cohort (Gwiazda et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In case of male and female populations it only differs by the evolution of localisations in the boundary cohorts. This simplification was already proposed in [3] for the single species case, whose convergence was proven in [9]. Here compared to [10], we simplified the EBT scheme further by choosing the localisation of the couples in the boundary cohorts consistently in terms of the localisations of the male and female populations.…”
Section: Relation Between the Methodsmentioning
confidence: 99%
“…The method has been popular for many years, even its convergence was proven only recently in [3], and in [9] where the rate of convergence was also shown. Results on the convergence were obtained using a theoretical approach to stability, where the underlying model is embedded in a space of nonnegative Radon measures (M + (R + )) equipped with a bounded Lipschitz distance (flat metric).…”
Section: Introductionmentioning
confidence: 99%
“…Remark: For the boundary condition (5) the system is not explicitly solvable since the boundary condition is dependent on the solution itself. In a version of EBT, or in fact very similar in this context splitting method, we use the following approximation (for a full description see [22,37,23,38]):…”
Section: Cohort Approachmentioning
confidence: 99%